The Violence of Peace: Ethnojustice in Northern Uganda. Issue 3 (20th April 2014) - Branch, Adam; Anders, Gerhard; Zenker, Olaf
ABSTRACT Traditional justice, or what this article refers to as 'ethnojustice', claims to promote social reconstruction, peace and justice after episodes of war by rebuilding traditional order. Ethnojustice has become an increasingly prominent mode of transitional justice in northern Uganda. As such interventions multiply throughout Africa, it is essential to probe their political and practical consequences. This article situates ethnojustice theoretically within the broader discourse, practice and institutions of transitional justice, and historically within the reaction against orthodox liberal transitional justice from within the industry. Through an engagement with ethnojustice texts and interventions in the Acholi region of northern Uganda, the article argues that ethnojustice can end up extending forms of unaccountable, patriarchal power within Acholi society, funded and supported by the Ugandan state and international donors. In addition to underpinning this project of social discipline, ethnojustice also benefits the Ugandan state in its effort to avoid accountability for its violence during the war.